Increasing Atlantic Ocean Heat Transport in the Latest Generation Coupled Ocean‐Atmosphere Models: The Role of Air‐Sea Interaction. Issue 11 (27th November 2018) - Grist, Jeremy P.; Josey, Simon A.; New, Adrian L.; Roberts, Malcolm; Koenigk, Torben; Iovino, Doroteaciro
Abstract: Recent increases in resolution of coupled ocean‐atmosphere models have the potential to improve the representation of poleward heat transport within the climate system. Here we examine the interplay between model resolution‐dependent changes in Atlantic Ocean heat transport (AOHT) and surface heat fluxes. The different roles of changes in atmospheric and ocean resolution are isolated using three different climate models (The Centro Euro‐Mediterraneo sui Cambiamenti Climatici Climate Model 2, Hadley Centre Global Environmental Model 3 – Global Coupled configuration 2, and European Community Earth‐System Model 3.1) and comparing runs in which (a) only the ocean resolution changes, (b) only the atmosphere resolution changes, and (c) both change. Enhancing ocean resolution from eddy parameterized to eddy permitting increases the AOHT throughout the basin, values changing from 1.0 to 1.2 PW at 26°N, bringing the AOHT into the range of estimates from the RAPID observing array. This increase in AOHT is associated with higher North Atlantic sea surface temperatures and increased ocean heat loss to the atmosphere. Increasing the atmospheric resolution alone has little impact on the AOHT due to regionally compensating changes in the components of the net heat flux. Finally, in a fourth experiment the impact of resolution changes in both components and the transition to an eddy‐resolving ocean is assessed. This additional resolution increase is accompanied by a further change in the AOHT and improves agreement with observations in the tropics but not the subpolar regions. However, unlike with the increase to the eddy‐permitting ocean, when the greatest AOHT change occurs in the subtropics and subpolar region, the most significant increase now occurs in the tropics. Plain Language Summary: The ocean and atmosphere export large amounts of heat from the tropics toward more poleward latitudes. In the Northern Hemisphere about 25% of this export is accomplished by the movement of water in the Atlantic Ocean. It is therefore important for climate models to accurately simulate this Atlantic Ocean heat transport (AOHT). However, historically climate models have typically underestimated AOHT relative to our best observations. This paper investigates how changing the size of the grid cells in the model changes both AOHT and the ocean‐to‐atmosphere exchange of heat in the model. Reducing the size of the grid cells in the models is referred to as increasing the resolution. Increasing the resolution of the ocean component of the model to 1/4° latitude and longitude increases AOHT, making agreement with observations better in the subtropics but slightly worse in subpolar regions. Increasing the resolution of the atmospheric part of the model had little effect on AOHT, instead bringing changes to different parts of the ocean‐to‐atmosphere heat exchange that compensate each other. Finally, we examined the AOHT in one of the newest climate models with even higher resolution (1/12° ocean and 25‐km atmosphere). Additional improvements in the simulation of AOHT were found. Key Points: Model resolution‐dependent changes in Atlantic Ocean heat transport and surface heat fluxes are determined using three climate models Increasing ocean resolution to eddy‐permitting raises Atlantic heat transport; changing atmospheric resolution only impacts surface fluxes Enhancing ocean resolution to eddy‐resolving results in a further increase in Atlantic Heat Transport and the best observational agreement